AN INTERVIEW WITH KAITLIN ANDERSON: DIFFERENCES IN DISCIPLINE - Shaughnessy, Michael; Wells, Robin (Acta Scientiae et Intellectus, 2024)
Kaitlin Anderson is Distinguished Doctoral Fellow in the Department of Education Reform at the University of Arkansas, 212 Graduate Education Building College of Education and Health Professions, Fayetteville, AR 72701. She can be reached at: kaitlina@uark.edu In this interview, she responds to questions regarding schools in America and disparities in discipline procedures. 1) Dr. Anderson, what first prompted you to investigate "disparate disciplinary outcomes"? It’s difficult for anyone who reads the news to not be aware of some of the racial disparities in school discipline policies, but my interest in this issue stems from the question: “are certain students being punished more harshly than their peers of different races, who commit the same infractions and in the same types of schools?” Most of the numbers we see frequently just focus on outcomes, which are often naively critiqued by just blaming the issue on the fact that certain kids are just “bad kids.” The problem with this view point is that, according to my research, there are still disparities even conditional on the type of infraction and within the same school.